2021
DOI: 10.1017/s0033291721000441
|View full text |Cite
|
Sign up to set email alerts
|

The genetic basis of major depression

Abstract: Major depressive disorder (MDD) is a common, debilitating, phenotypically heterogeneous disorder with heritability ranges from 30% to 50%. Compared to other psychiatric disorders, its high prevalence, moderate heritability, and strong polygenicity have posed major challenges for gene-mapping in MDD. Studies of common genetic variation in MDD, driven by large international collaborations such as the Psychiatric Genomics Consortium, have confirmed the highly polygenic nature of the disorder and implicated over 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 160 publications
(205 reference statements)
0
55
0
2
Order By: Relevance
“…Increasing sample sizes may yield more significant SNP-by-environment interactions, but the highly polygenic nature of depression makes searching for polygenic-environment interactions appealing. Investigations of G-E interactions using depression PRSs have demonstrated null or conflicting results (Kendall, et al, 2021), and these PRS-environment interaction analyses have not modelled a residual trend in the variability of outcome, which can bias G-E interaction estimates (Dahl, et al, 2020). Additionally, the SNP effects used to construct a PRS are estimated assuming an additive genetic model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing sample sizes may yield more significant SNP-by-environment interactions, but the highly polygenic nature of depression makes searching for polygenic-environment interactions appealing. Investigations of G-E interactions using depression PRSs have demonstrated null or conflicting results (Kendall, et al, 2021), and these PRS-environment interaction analyses have not modelled a residual trend in the variability of outcome, which can bias G-E interaction estimates (Dahl, et al, 2020). Additionally, the SNP effects used to construct a PRS are estimated assuming an additive genetic model.…”
Section: Discussionmentioning
confidence: 99%
“…The core symptoms of depression are persistent low mood and anhedonia, with other diagnostic signs and symptoms including changes in cognition, appetite, or sleep, and feelings of fatigue and worthlessness. The heritability of MDD is lower than many other psychiatric disorders, estimated at between 30-40%, with higher values for severe cases (Kendall, et al, 2021). This lower heritability suggests that a substantial proportion of liability to depression is due to environmental risk factors.…”
Section: Introductionmentioning
confidence: 92%
“…Indeed, numerous studies have pointed to epigenetic changes related to early-life experiences in the occurrence of depression and anxiety ( Farrell et al., 2018 ). It is now understood that although the contribution of individual gene variants is small, current evidence indicates that genome-wide influences on MDD can vary with stressful life experiences ( Kendall et al., 2021 ). In this regard, a large-scale genome-wide study showed strong associations between polygenic risk scores and major depression among individuals exposed to childhood trauma and socioeconomic adversity ( Shen et al., 2020 ).…”
Section: Considering Context and Experiencesmentioning
confidence: 99%
“…In this regard, a large-scale genome-wide study showed strong associations between polygenic risk scores and major depression among individuals exposed to childhood trauma and socioeconomic adversity ( Shen et al., 2020 ). Conversely, social support/social cohesion was accompanied by reduced relations with polygenic risk scores and MDD among individuals who had encountered significant stressors ( Choi et al., 2020 ; Kendall et al., 2021 ). Evidently, interactions exist between genetic factors and childhood trauma, socioeconomic adversity, and social support in risk of MDD.…”
Section: Considering Context and Experiencesmentioning
confidence: 99%
“…Major Depressive Disorder (MDD) is a prevalent, burdensome and heterogeneous disorder with a complex etiology of genetic and environmental determinants (Kendall et al, 2021). In recent years, evidence has accumulated with regard to the ubiquity of pleiotropy across the genome (Watanabe et al, 2019), and shared genetic etiology is thought to play a large role in the widespread comorbidity among psychiatric disorders and risk factors (van Rheenen, Pevrot, Schork, Lee, & Wray, 2019).…”
Section: Major Depressive Disorder and Lifestyle: Pleiotropic Effects In Bivariate Genetic Analyses Of Extended Twin Pedigreesmentioning
confidence: 99%